2018
DOI: 10.1021/acssuschemeng.8b04835
|View full text |Cite
|
Sign up to set email alerts
|

A High-Capacity, Reversible Liquid Organic Hydrogen Carrier: H2-Release Properties and an Application to a Fuel Cell

Abstract: Hydrogen storage in the form of a liquid chemical is an important issue that can bridge the gap between sustainable hydrogen production and utilization with a fuel cell, which is one of the essential sectors in the hydrogen economy. Herein, the application of a potential liquid organic hydrogen carrier, consisting of biphenyl and diphenylmethane, is demonstrated as a safe and economical hydrogen storage material. The presented material is capable of a reversible storage and release of molecular hydrogen with 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…gasification of biomass/biofuels and water splitting), it is mostly produced via steam reforming process, which indeed is not sustainable because it uses fossil fuels and CO 2 is produced [8]. Moreover, aside from that, there are also significant limitations related to its difficult storage and delivery [9], as well as safety issues derived from its high flammability and potential explosiveness [10]. A promising alternative to overcome those limitations is the production of H 2 from hydrogen carrier molecules.…”
mentioning
confidence: 99%
“…gasification of biomass/biofuels and water splitting), it is mostly produced via steam reforming process, which indeed is not sustainable because it uses fossil fuels and CO 2 is produced [8]. Moreover, aside from that, there are also significant limitations related to its difficult storage and delivery [9], as well as safety issues derived from its high flammability and potential explosiveness [10]. A promising alternative to overcome those limitations is the production of H 2 from hydrogen carrier molecules.…”
mentioning
confidence: 99%
“…Therefore, mixing biphenyl and diphenylmethane to a eutectic composition allows the material to be liquid at ambient temperatures and still provides a high hydrogen storage capacity (6.9 wt%, 60 g-H 2 L −1 ). The hydrogenation reaction of 1 to a hydrogen-rich mixture 2 and the dehydrogenation of 2 to 1 were demonstrated successfully with a high conversion over 94% with the aid of proper catalysts [10,11] . DFT calculations indicated that dicyclohexylmethane requires a higher temperature (603 K) than bicyclohexyl (568 K) for complete dehydrogenation [11] .…”
mentioning
confidence: 99%
“…The hydrogenation reaction of 1 to a hydrogen-rich mixture 2 and the dehydrogenation of 2 to 1 were demonstrated successfully with a high conversion over 94% with the aid of proper catalysts [10,11] . DFT calculations indicated that dicyclohexylmethane requires a higher temperature (603 K) than bicyclohexyl (568 K) for complete dehydrogenation [11] . The addition of diphenylmethane to biphenyl provides a clear advantage of 1 to be in a liquid phase but its hydrogen-rich analogue dicyclohexylmethane provides a drawback of 2, operating at a high reaction temperature upon H 2 release.…”
mentioning
confidence: 99%
See 2 more Smart Citations